Cloning and sequence analysis of pep-carboxylase from cassava - Tenjo F, FA; Mayer, Jorge Edgard (International Center for Tropical Agriculture, 1993)
Cassava (Manihot esculenta Crantz) is very drought tolerant and hows high levels of photosynthesis at high temperatures. This makes cassava an important source of carbohydrates for several arid regions, especially in Africa. Some varieties perform better than others. Physiological performance, which covers a wide range between C3 and C4 plants, could be increased through directed breeding. In order to do so, a better understanding of the underlying molecular mechanisms is needed, as to develop well defined breeding criteria and tests that could aid to that purpose. Several enzymes are involved in the fixation of CO2 in plants, phosphoenolpyruvate carboxylase playing a central role. We want to analyze the compartmentation of this and other photosynthetic enzymes between palisade and mesophyll cells by using in situ hybridization of the radiolabelled genes on histological sections. For this purpose the homologou gene must be isolated. We constructed a cassava genomic DNA library from the variety 996 CIAT in an EMBL 3 derived bacteriophage cloning vector. The library was screened with a maize ppc probe (obtained from T. Nelson, Yale), and after three rounds of purification, a putative cassava ppc clone of 10 kb was obtained. We are in the process of mapping and sequencing our clone. The next steps will include carrying out Northern analysis to assess levels of expression in different varieties, carrying out relatedness studies with other sequence characterized ppc genes, and the establishment of in situ hybridization techniques.